Fast and slow myosins as markers of muscle injury - Guerrero, M.; Guiu-Comadevall, M.; Cadefau, J. A.; Parra, J.; Balius, R.; Estruch, A.; Rodas, G.; Bedini, J. L.; Cusso, R. (British Journal of Sports Medicine, 2008)
Objective: The diagnosis of muscular lesions suffered by athletes is usually made by clinical criteria combined with imaging of the lesion (ultrasonography and/or magnetic resonance) and blood tests to detect the presence of non-specific muscle markers. This study was undertaken to evaluate injury to fast and slow-twitch fibres using specific muscle markers for these fibres.